The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/f11080837
|View full text |Cite
|
Sign up to set email alerts
|

Non-Thermal Plasma Can Be Used in Disinfection of Scots Pine (Pinus sylvestris L.) Seeds Infected with Fusarium oxysporum

Abstract: The aim of this study was to use diffuse coplanar surface barrier discharge (DCSBD) non-thermal plasma for the disinfection of pine seed surfaces infected with Fusarium oxysporum spores. Artificially infected seeds of Scots pine (Pinus sylvestris L.) were treated with plasma for the following exposure times: 1 s, 3 s, 5 s, 10 s, 15 s, 20 s, 30 s, and 60 s, and subsequently germinated on agar medium in Petri dishes at room temperature for the estimation of seed germination and disinfection effect of plasma trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…Several authors have shown that non-thermal plasmas are able to control seed-transmitted pathogens, such as Aspergillus parasiticus Speare, Penicillium sp. in bean (Rüntzel et al 2019), in addition to pathogens from chickpea, lentil, soybean (Selcuk et al 2008;Pérez-Pizá et al 2018, Taheri et al 2020, Pérez-Pizá et al 2021, peanut (Devi et al 2017), Scots Pine (Swiecimska et al, 2020), onion (Kopacki et al 2017), rice (Jo et al 2014) and pepper (Ahmad et al 2022). Non-thermal plasma, when applied to Fabaceae seeds under low stress, is beneficial for seed germination and seedling growth (Será et al 2021, Yan et al 2022, as the results found by Pérez-Pizá et al (2019) in which it improved the germination of soybean seeds.…”
Section: Physical Treatmentmentioning
confidence: 98%
“…Several authors have shown that non-thermal plasmas are able to control seed-transmitted pathogens, such as Aspergillus parasiticus Speare, Penicillium sp. in bean (Rüntzel et al 2019), in addition to pathogens from chickpea, lentil, soybean (Selcuk et al 2008;Pérez-Pizá et al 2018, Taheri et al 2020, Pérez-Pizá et al 2021, peanut (Devi et al 2017), Scots Pine (Swiecimska et al, 2020), onion (Kopacki et al 2017), rice (Jo et al 2014) and pepper (Ahmad et al 2022). Non-thermal plasma, when applied to Fabaceae seeds under low stress, is beneficial for seed germination and seedling growth (Será et al 2021, Yan et al 2022, as the results found by Pérez-Pizá et al (2019) in which it improved the germination of soybean seeds.…”
Section: Physical Treatmentmentioning
confidence: 98%
“…They also found that Alternaria and Epicoccum species were the most resistant to plasma [152]. NTP also disinfected seeds artificially inoculated with spores of phytopathogenic fungi, such as Alternaria alternata, Aspergillus flavus, Aspergillus niger, Aspergillus parasiticus, Cladosporium fulvum, Fusarium circinatum, Fusarium culmorum, Fusarium fujikuroi, Fusarium oxysporum, Penicillium decumbens, Penicillium verrucosum, and Rhizoctonia solani [46,78,82,83,85,[94][95][96][97][98][99][100]. Although the sensitivity to the plasma was not significantly different among the fungal species, subtle differences were observed.…”
Section: Inactivation Of Fungi In Agriculture and Foodsmentioning
confidence: 99%
“…Plasma potential for its use in agriculture is extensive. There are a lot of possibilities for its utilization, e.g., plasma treatment of seeds causing their disinfection [10,15,17] or stimulation of their germination capacity [10]. Using plasma, nitrogen from air can be captured, held and incorporated into water.…”
Section: Introductionmentioning
confidence: 99%